Peasantry and State Policy in the Field of Alcohol Sales in Russia at the Beginning of the 20th Century - I. A. Shevchenko (Научный диалог)
The article is devoted to the problem of finding optimal mechanisms for the struggle for national sobriety in Russia at the beginning of the 20th century. Various aspects of government policy in relation to the distribution of alcohol (public sale of drinks), legislative measures discussed in the State Duma and the State Council, and peasant practice of controlling the circulation of alcoholic beverages are examined. The main attention is paid to the struggle of the Russian peasantry for the right to control the work of the drinking establishment in the village, prohibiting or allowing its work by the decision of the rural society. It is concluded that the power in Russia followed paternalistic guidelines in the field of alcohol sales at the beginning of the 20th century, not trusting the possibilities of rural self-government to regulate this process in the direction of the development of a sober culture. The study is based on diverse sources, such as archival data, published information - statistics, legislative acts, verbatim records of meetings of the State Duma and the State Council, periodicals. The article uses the problem-chronological method and the comparative analysis method. The novelty of the study is a comparison of state temperance measures and peasant practices in this area.